IMPLEMENTASI PERATURAN BUPATI NO 45 TAHUN 2021 TENTANG PENYERAHAN PRASARANA, SARANA DAN UTILITAS PERUMAHAN DI KABUPATEN PROBOLINGGO - Mamik Kusia; Hadi Susanto; Sri Mulyani (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2023)
This research is to analyze the implementation of Regent Regulation No. 45 of 2021 concerning Handover of Housing Infrastructure, Facilities and Utilities in Probolinggo Regency. The design of this research is descriptive qualitative. The results of the research show that the implementation of Probolinggo Regent Regulation Number 45 of 2021 in Probolinggo Regency has been going quite well, with the implementation of programs/activities/sub-activities in the affairs of housing PSU management in Probolinggo Regency and there has been an increase in the handover of housing PSU at the end of 2021 in a total of seven PSU areas as well as plans to hand over 18 housing PSUs in 2022. The policy for handing over housing PSUs in Probolinggo Regency has weaknesses and obstacles including, there has not been socialization of policy actors, especially housing developers and community members in residential areas, lack of human resources handling the handing over of housing PSUs, the absence of Standard Operating Procedures (SOP) in the submission of housing PSU and the lack of supervision and control over the delivery of housing PSU in Probolinggo Regency.